Is science, technology, engineering and mathematics in higher education sexist and racist? All surface, no substance. Issue 2 (11th August 2022) - ElMorally, Reham; Wong, Billy; Copsey-Blake, Meggie
Scholars have long argued there is systemic injustice within higher education, particularly with regards to ethnic and gender disparity in Science, Technology, Engineering and Mathematics (STEM) education (Race, 2005; Rollock and Gillborn, 2011; Singh, 2011; Gillborn et al., 2016; Arday and Mirza, 2018; Bhopal and Henderson, 2019a; Advance HE, 2021a). In the UK, 35% of STEM students are female, but STEM disciplines are not innocent of bias and a females' ethnic background poses another hindrance to their academic and career trajectories (Bosworth and Kersley, 2015). Existing studies have highlighted institutional bias towards White male students and applicants, and it is undeniable that there is a myriad of gendered and racial biases, especially in the physical sciences. Using data collected over a two-year period, 69 qualitative interviews were coded and analysed from an England-based University to gain further insights and add to existing literature concerning racism and sexism in STEM degrees. This article argues that the UK is currently experiencing the 'height of capitalism', where the value of labour is considerably disproportionate. This can act as a demoralizing force against inclusivity within STEM disciplines. The race and gender gaps, particularly in terms of attainment, are two of the most significant avenues where we see the value of labour diminished, and capitalism pronounced. In addition to racial and gender biases, institutionalised racism and systemic injustices embedded within the higher education system has doubled, if not more, the burdens and barriers women and ethnic minorities in STEM face (Jones, 2019). This paper is not a crusade against corporations, but an investigation into the intersectionality of gender and race in relation to opportunity discrepancy and attainment, to better understand why large discrepancies in inclusivity is more pronounced in STEM disciplines and professions. The research explores the themes of microaggression as a possible explanation for attainment gaps, attitudes towards affirmative action and positive discrimination and the policy's attempt in mediating systemic injustices through representation, and introspectively unpacks its effects on students' potential career opportunities in the capitalist labour market.